KAJIAN PERBEDAAN PREVALENSI BALITA KURUS DAN PENDEK MENURUT STANDAR WHO 2005 DIBANDING NCHS: Analisis Data SKRT 2004 - ., Sandjaja (GIZI INDONESIA, 2008)
THE DIFFERENCE IN THE PREVALENCE OF WASTING AND STUNTING IN CHLIDREN AGE0-59 MONTHS BY USING NCHS AND NEW WHO ANTHROPOMETRIC STANDARD: Re-analysis of Indonesian Household Health Survey 2004WHO introduced new Child Growth Standard for children 0 – 60 months of age in the early 2006based on Multi-Centre Growth Reference Study (MGRS) in 6 countries: Brazil, Ghana, India,Norway, Oman and the United States of America involving healthy children living in healthyenvironment that provide possibility for them to grow according to their genetic potential. WHOrecommended that the standard be used as a new anthropometric reference replacing the existingNCHS-WHO child growth reference. However, some experts demand to evaluate the standard,before Indonesia adopts it in the nutrition program. This paper tries to compare the consequenceof adopting new WHO standard to the magnitude of stunting and wasting. The main objective ofthe paper is to re-analyze the existing anthropometric data on children aged 0-59 months by usingboth NCHS-WHO reference and new WHO standard on the prevalence of wasting (W/L or W/H)and stunting (H/A). This re-analysis is based on anthropometric data of 3,316 children age below 5years old from Household Health Survey 2004. Child weight and length/height were converted intoz-scores of W/H and H/A by using both NCHS and new WHO Growth Standard, and compared theprevalence of wasting and stunting. The results showed that the prevalence stunting is higher byusing new WHO Growth Standard (28.6%) compared to that by using NCHS growth references(24.1%). The difference in the prevalence varied between sex from 4.5-4.7% and across agegroups from 1.3-9.2%. Similar results also found for the prevalence of wasting. The prevalence ofwasting by using WHO Growth Standard and NCHS growth references was 15.1% and 13.8%respectively. The difference in the prevalence varied between sex from 0.8-2.1% and across agegroups which varied fourfold (21.0% and 5.6%) for children age below 6 month old and only 1.7%for children age 48-59 month old.Keywords: anthropometric standard, stunted, wasted, height for age, weight for height